The industrialization of design : a history from the steam age to today - Gantz, Carroll, 1931- (Jefferson, N.C. : McFarland, 2011)
"Industrial design is a fundamental component of the traditional consumer experience. This book traces the history of industrial design over three centuries, beginning with the eighteenth-century industrial revolution. It identifies the major figures, organizations, styles and evolutionary events of the profession"--
Pre-1800: Twin revolutions -- 1800-1850: The American system -- 1850-1875: International competition -- 1875-1900: The "new" decorative art -- 1900-1918: Architects take the lead -- 1918-1927: Modern design takes root -- 1927-1936: American modern design -- 1936-1945: Dreams of the future and war -- 1945-1950: Postwar recovery and consolidation -- 1950-1965: Imports and contradictions -- 1965-1985: Challenges and computers -- 1985-2010: Global design -- Appendix I. Biographies -- Appendix II. Past presidents of industrial design organizations.
Includes bibliographical references and index.
Keywords: Industrial design -- History; Product design -- History; Technology -- History